1983
DOI: 10.1088/0022-3719/16/36/011
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of Compton scattering for MgO. I. Momentum density, Compton profiles, and B-functions

Abstract: On the basis of augmented-plane-wave band-structure calculations for the insulating compound MgO the authors have calculated the momentum density. Compton profiles, and B(z) functions. In order to derive physical insight from the results they have put much effort into understanding the momentum density in terms of real-space wavefunctions and nearest-neighbour interactions. To this end they performed a backtransformation of the momentum densities into real space, thus obtaining Wannier-like functions. The Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…1, both with the experimental anisotropy showing the largest deviations at small Pz and also for the largest peak at 1-2 a.u. Similar deviations were found for MgO (Aikala et al, 1982;Podloucky & Redinger, 1984). This is surprising for NaF, because it is supposed to be an almost ideal candidate for an ionic crystal and because in the case of the spherically averaged Compton profiles the agreement between the experiment and LCAO model was good (Paakkari & Halonen, 1978).…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…1, both with the experimental anisotropy showing the largest deviations at small Pz and also for the largest peak at 1-2 a.u. Similar deviations were found for MgO (Aikala et al, 1982;Podloucky & Redinger, 1984). This is surprising for NaF, because it is supposed to be an almost ideal candidate for an ionic crystal and because in the case of the spherically averaged Compton profiles the agreement between the experiment and LCAO model was good (Paakkari & Halonen, 1978).…”
Section: Resultssupporting
confidence: 62%
“…In our previous study on MgO (Aikala, Paakkari & Manninen, 1982;Podloucky & Redinger, 1984) we found a discrepancy between the experimental data and both LCAO and APW theories expressed in terms of the Compton profile and autocorrelation function. Despite the laborious effort, including the use of various kinds of wave functions for the 02-ion, the problem was not solved.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…In a recent paper Podloucky & Redinger (1984) reported electron momentum distribution (EMD) and Compton profile curves for MgO as obtained by an augmented-plane-waves calculation. Unfortunately the data are not tabulated, so that a point-topoint comparison is impossible; nevertheless, the essential features in the three directions are very similar to the present ones: the [111] curve is intermediate between the other two; the peak in the [100] direction is the broadest, and is shifted to higher (Weiss, 1970;Togawa et al, 1971) are quite unreliable because of the fact that with X-rays multiple scattering events are important, and the impulse approximation fails for 1 s electrons, useful information is provided by more recent y-ray measurements (Berggren et al, 1977;Aikala et al, 1982).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, residual experimental errors could be at the origin of the difference; in this respect it must be noticed that at low momenta Aikala's curve is appreciably lower (and nearer to ours) than the lessrecent one (Berggren et al, 1977). A deeper comparison with the experimental data, and with the theoretical results of Podloucky & Redinger (1984), including an analysis of the anisotropy, of the autocorrelation function (Schiilke, 1977;Pattison & Williams, 1976), and of basis-set effects would require much more space and is deferred to another paper.…”
Section: Resultsmentioning
confidence: 99%